Direct bulk-fill resin composite restorations: Characterization of pulpal floor gaps in deep occlusal cavities and current restorative minimization strategies - An overview - Khamis A Hassan; Salwa E Khier (Wolters Kluwer Medknow Publications, 2023)
Aims: This paper provides a thorough overview on the debonding problem and gap formation at pulpal floors in deep occlusal cavities restored directly with bulk-fill resin composites. It also reviews the techniques currently available in the literature for reducing this problem. Introduction: When a single mass of bulk-fill resin composite is inserted in a deep occlusal cavity and light cured, it undergoes restrained shrinkage due to bonding to surrounding cavity walls. This shrinkage generates stresses within the mass which are not uniformly distributed due to variations in adhesive bonding to enamel and dentin of surrounding cavity walls. This behavior creates a problem of internal debonding and gap formation at the pulpal floor that results in postoperative sensitivity and persistent tooth pain, as well as failure of the restoration, over the time, due to biodegradation of resin-dentin bond. Materials and Methods: The data was searched and collected from 2021-2022. A total of 51 articles were included in this review. Results and Discussion: Three restorative techniques were recently reported as possible solutions for this problem, all aiming at relieving the developed shrinkage stresses and reducing the pulpal floor gap formation. In the first technique, an intermediate layer of bulk-fill resin composite was placed on the pulpal floor and cured. While in the second technique, a fiber-reinforced layer of bulk-fill resin composite was placed on the pulpal floor and cured. In these two techniques, the restoration was completed by filling the cavity with a mass of bulk-fill resin composite and curing it. As for the third technique "the semi-split bulk-filling technique", a diagonal gap was cut in the uncured mass of bulk-fill resin composite, extending halfway in pulpal direction through the composite bulk, followed by curing. Then, the created gap was filled with the same bulk-fill resin composite to complete the restoration and followed by curing. Conclusion: The three restorative techniques reported in this paper are possible solutions to the problem of debonding and gap formation at pulpal floors in deep occlusal cavities restored directly using bulk-fill resin composites. They all relieve the developed shrinkage stresses and reduce the pulpal floor gap formation.